(untitled) (Bangladesh Journal of Microbiology, 2010)
Bird flu, synonym of avian influenza (AI) caused by influenza A virus, become concern across the world for the possible incidence of the next human influenza pandemic. The latent danger of AI pandemic remains very real, though, the precise timing of occurrence and severity is uncertain. Each avian influenza type A (AIA) contains one of the 16 subtypes of haemagglutinin (HA) and 9 neuraminidases (NA) implicating theoretically 144 subtypes of AIA are possible in circulation, but only H1N1, H2N2 and H3N2 subtypes are documented for past pandemics in humans. In recent years H5N1, H7N3, H7N2, H7N7 and H9N2 are isolated from human samples, though H1N1 and H3N2 are still in circulation. Avian influenza viruses preferentially recognize receptor containing sialosugar chains terminating in sialic acid ?-2,3-galactose in bird, whereas, human preferentially contain ?-2,6-galactose subtype-receptor. To initiate a pandemic outbreak in human, the AIA viruses need alteration of receptor recognition specificity; and perfect match between HA and NA along with optimal cellular tropism. Cyclic nature of bird-flu emergence, and moreover, sporadic human incident reported around Asia and Europe in recent years anticipating a pandemic appearance of bird-flu in time to come. As we are on the edge of this alarming situation, AI prevention and containment can be considered under categories of surveillance, intervention, antiviral drugs, vaccination together with environment management issues. Keywords: Pandemic; Avian influenza; Genetic reassortment; Host specificity; Environment management DOI: http://dx.doi.org/10.3329/bjm.v25i1.4847 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 1-8